2022
DOI: 10.21203/rs.3.rs-1871438/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sildenafil for congenital heart diseases induced pulmonary hypertension, a meta-analysis of randomized controlled trials.

Abstract: Background: PDE5 inhibitors (PDE5-Is) manifest its effects by inhibiting the PDE5 dependent cGMP hydrolysis, thus increasing cGMP intracellularly which results in vascular smooth muscles relaxation and vasodilatation. PDE 5 inhibitors, such as sildenafil, were first prescribed for angina pectoris then for erectile dysfunction (ED). Recently, sildenafil has been proposed in congenital heart diseases (CHD) induced PAH, which constitute a huge burden on children health and can attribute to fatal complications du… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Recent improvements in medical treatments, surgical procedures, imaging, and pediatric intensive care helped more than 90% of congenital heart disease (CHD) children reach adulthood and decreased the total mortality rate by 31%in the previous 20 years. [2,3] This changes our focus on CHD from mortality to morbidity, where although babies born with CHD now have a longer life expectancy and better quality of life, they are more likely to have psychological distress, neurocognitive deficits, and social challenge. Studies reported that approximately 30% had mood or anxiety disorders and 20% showed symptoms comparable with posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in medical treatments, surgical procedures, imaging, and pediatric intensive care helped more than 90% of congenital heart disease (CHD) children reach adulthood and decreased the total mortality rate by 31%in the previous 20 years. [2,3] This changes our focus on CHD from mortality to morbidity, where although babies born with CHD now have a longer life expectancy and better quality of life, they are more likely to have psychological distress, neurocognitive deficits, and social challenge. Studies reported that approximately 30% had mood or anxiety disorders and 20% showed symptoms comparable with posttraumatic stress disorder.…”
Section: Introductionmentioning
confidence: 99%